Informant‐reported subjective cognitive decline is specifically relevant in MCI patients: Association with cognition, amyloid deposition and neurodegeneration. (31st December 2021) - Kuhn, Elizabeth; Perrotin, Audrey; Touron, Edelweiss; Dautricourt, Sophie; Vanhoutte, Matthieu; Vivien, Denis; De la Sayette, Vincent; Chetelat, Gaël; ,
Abstract: Background: Informant‐reported subjective cognitive decline (I‐SCD) have been associated with objective cognitive decline and biomarkers of Alzheimer's disease (AD) in previous studies. However, we lack a comprehensive overview of these associations across the entire clinical continuum of the Alzheimer's syndrome allowing to stress whether there is a clinical stage where this measure is particularly relevant. This study aims at describing the relationships of I‐SCD to cognition and multimodal neuroimaging data within two independent cohorts. Method: We used data from 110 participants from IMAP+, and, as an independent replication cohort, from 731 participants from ADNI. All participants were divided into four clinical groups (IMAP+/ADNI): controls (N=32/157), subjective cognitive decline (SCD; N=25/84), mild cognitive impairment (MCI; N=35/369) and dementia (N=18/121). We first compared the I‐SCD score between groups and assessed its relationship to cognition within each clinical group cross‐sectionally and longitudinally (over 2.5 years). We then assessed the voxelwise relationships between the I‐SCD score and neuroimaging measures of amyloid deposition (Florbetapir‐PET) and neurodegeneration, i.e. atrophy (T1‐MRI) and hypometabolism (FDG‐PET), across the four clinical groups. These analyses were performed in IMAP+ and replicated in the ADNI cohort. Results: The I‐SCD score was higher from one clinical group to another within both cohorts (p?0.001, except SCD‐MCI p=0.15 in IMAP+). Interestingly, this measure was associated with cognition and AD biomarkers specifically within the MCI patients. The relation was such that higher I‐SCD was associated with lower memory and global cognition cross‐sectionally and over time (Figure 1), higher amyloid deposition (global SUVr and voxelwise) and higher neurodegeneration (Figure 2). The same findings were recovered in both cohorts, except for neurodegeneration where the links were significant in ADNI only. Conclusion: Our findings reveal that the cognitive decline reported by the informant is particularly meaningful at the MCI stage, when the corresponding self‐reported score is contaminated by decreased awareness. The strong and consistent links with cognition and AD biomarkers found here reinforce the validity and clinical relevance of this finding and suggest that this measure should be used in clinical trials to identify MCI patients at higher risk to develop cognitive decline and/or AD.